The effect of meditation on shooting performance - Solberg, E. E.; Berglund, K. A.; Engen, O.; Ekeberg, O.; Loeb, M. (British Journal of Sports Medicine, 1996)
OBJECTIVE: To study effects of meditation on the shooting performance. METHODS: 25 elite shooters were investigated in an independent groups design. The results in standardised test shootings indoors and in ordinary competitions outdoors were assessed before and after regular meditation training for the experimental group. The experience of tension during the test shootings was self recorded on a visual analogue scale (VAS). RESULTS: The competition results in the outdoor season (1993), just after the meditation training period, compared with the results the previous season (1992), were better in the meditation group (P < 0.05). No significant difference between the groups was observed in the test shootings before and after the relaxation intervention. A significant association was shown between low tension and the results in the test shootings (correlation r = 0.42, P < 0.0001; Wilcoxon rank sum test, z = -3.36, P < 0.001); 18% (= r2) of the variance in performance was explained by tension. CONCLUSIONS: Meditation may enhance competitive shooting performance